Presenting an Optimal Model for Effective Implementation of Policy Principle 44 in Iran's Banking Industry - Jamali Kakroudi, Rohallah; Givarian, Hasan; Rabiei Mondejin, Mohammad Reza; Momeni, Mandan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  In the realm of economic policies, the banking system is a significant tool for implementing government economic policies. This research aimed to present an optimal model for the effective implementation of Policy Principle 44 in Iran's banking industry.Methodology: This qualitative study utilized thematic analysis. The statistical population included 18 academic experts and senior privatization specialists selected through purposive sampling. The research tool was semi-structured interviews, validated through face validity and reliability confirmed with an inter-coder agreement coefficient of 0.86.Findings: Results indicated three main dimensions: management system implementation, electronic government, and contextual factors. The nine key components were planning and resource mobilization, transfer process, management and execution network, monitoring and evaluation, private sector management, technological infrastructure, provision of new services, laws and regulations, and institutional-structural infrastructure as elements of the effective implementation model of Principle 44 in Iran's banking industry.Conclusion: The optimal model for the effective implementation of Policy Principle 44 in Iran's banking industry requires various factors and elements. Attention to these factors is crucial for the progress of Iran's banking system.